Development of Interactive Learning Media Using Articulate Storyline 3 Integrated with Problem Based Learning to Enhance Students' Critical Thinking on Temperature and Heat Concepts - Mithasari, Anggita Dewi Mithasari; Wiyatmo, Yusman (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study aims to develop interactive learning media utilizing Articulate Storyline 3 integrated with a problem-based learning (PBL) model to enhance students' critical thinking skills, particularly on the topic of temperature and heat. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. A large-scale field trial was conducted involving 100 eleventh-grade students from MAN 3 Banyumas. The implementation phase adopted a pretest-posttest control group design to measure the media's effectiveness. The results showed that the developed media is highly practical, as indicated by an average score of 90.43% from students and 93.05% from physics teachers, categorized as